Ergosterol and Water Changes in Tricholoma matsutake Soil Colony during the Mushroom Fruiting Season - Koo, Chang-Duck (The Korean Society of Mycology, 2009)
The purpose of this study is to understand spatio-temporal changes of active fungal biomass and water in Tricholoma matsutake soil colonies during the mushroom fruiting season. The active fungal biomass was estimated by analyzing ergosterol content at four different points within four replicated locations in a single circular T. matsutake colony at Ssanggok valley in the Sogri Mt. National Park in Korea during 2003 to 2005. The four points were the ahead of the colony, the front edge of the colony and 20 cm and 40 cm back from the front edge of the colony. Ergosterol content was 0.0 to 0.7 µg per gram dried soil at the ahead, 2.5 to 4.8 µg at the front edge, 0.5 to 1.8 µg at the 20 cm back and 0.3 to 0.8 µg at the 40 cm back. The ergosterol content was very high at the front edge where the T. matsutake hyphae were most active. However, ergosterol content did not significantly change during the fruiting season, September to October. Soil water contents were lower at the front edge and 20 cm back from the front edge of the colony than at the ahead and 40 cm back during the fruiting season. Soil water content ranged from 12 to 19% at the ahead, 10 to 11% at the edge, 9 to 11% at the 20 cm back and 11 to 15% at the 40 cm back. Our results suggest that the active front edge of the T. matsutake soil colony could be managed in terms of water relation and T. matsutake ectomycorrhizal root development.